Microstrip Circularly-Polarized Leaky-Wave Antenna with Wide Axial Ratio Bandwidth for X-Band Application - Wang, Z.; Zhang, D.; Gao, M.; Liu, H.; Fang, S. (Radioengineering Society, 2024)
A microstrip circularly polarized (CP) leaky-wave antenna (LWA) operating in the X-band, and having the characteristics of a broad axis-ratio bandwidth is proposed. The proposed LWA is made up of 13 unit cells in series through microstrip feeding lines. Elliptical and rectangular slots are etched in each unit cell to achieve the radiation of CP waves. The open stopband at the broadside frequency can be suppressed by shifting the feeding line position and etching two circular notches on both sides of each radiation patch. To validate the proposed method, a prototype antenna operating in the X-band is manufactured and measured. The measured result demonstrates that the â’10-dB impedance bandwidth of the microstrip CP LWA is 42.2% (7.96-12.22 GHz); the 3-dB axial ratio bandwidth is 26.4% (9.2-12.2 GHz); the gain of the antenna is 16.0 dBic. Besides, the main beam maintains good CP radiation properties while it continues to scan from â’22Â° to +18Â°.
Keywords: Leaky-wave antenna; circular polarization; open stopband; axial ratio bandwidth